'n Tegniek vir die identifisering van mense se konsepte van God - F. J. van Jaarsveld; J. Janse van Rensburg (Acta Theologica)
Man’s concepts of God occupy an important place in pastoral counselling. However, the identification of concepts of God is complex. Various efforts are reported. In this article an adjusted form of the repertory grid is discussed as a technique for the identification of man’s concepts of God. Empirical research about concepts of God by means of an adjusted form of the repertory grid is reported. This includes the development and evaluation of a category system for the interpretation of personal constructs regarding concepts of God. The results of the empirical research prove the suitability of the adjusted form of the repertory grid for the identification of concepts of God both in individuals and tendencies among groups of individuals.